Analysis of the Relationship Between Earthquake Events and the Disturbance of Ionosphere by Using IGS TEC - Nawaphon Phansori; Piyanon Boatong; Sirinil Phukrongta; Onuma Kriamthaisong; Prasert Kenpankho (ASEAN Journal of Science and Engineering Education, 2021)
This research aims to study and analyse the relationship between earthquake events and the disturbance of the ionosphere. The method for this research is to use the International GNSS Service (IGS) network to get Total Electron Content (TEC) in the ionosphere and then find the correlation between earthquake events and ionosphere characteristics. The result is correlated at 0.089, which shows the evidence of correlation on earthquake magnitudes and ionosphere. For future work, the researchers will study an impact on the development of an earthquake warning system.